An insight into major signaling pathways and protein–protein interaction networks involved in the pathogenesis of gestational diabetes mellitus. Issue 8 (22nd March 2022) - Chatterjee, Bhaswati; Neelaveni, Kudugunti; Kenchey, Himaja; Thakur, Suman S.
Abstract: Gestational diabetes mellitus (GDM) is associated with the increase of glucose in the blood rather than being absorbed by the cells. A better understanding of the signaling pathways is necessary to understand the pathophysiology of GDM. This study provides details about a series of signaling pathways and protein–protein interactions involved in the pathogenesis of GDM and their evaluations in GDM development. Protein–protein interactions were found between proteins of several signaling pathways that suggest interlink between these signaling pathways. Protein–protein interactions were generated with high confidence interaction scores based on textmining, cooccurrence, coexpression, neighborhood, gene fusion, experiments, and databases. The dysregulation of signaling pathways may also contribute to the increased risk of complications associated with GDM in the mother and child. Further, studies on signaling pathways involved in the pathogenesis of GDM would help in the development of an effective intervention to prevent GDM along with the identification of key targets for effective therapies in the future.